CONSTITUCIONALISMO DIGITAL: ENTRE REALIDAD DIGITAL, PROSPECTIVA TECNOLÓGICA Y MERA DISTOPÍA CONSTITUCIONAL - Barrilao, Juan Francisco Sánchez (Revista da AJURIS - Qualis A2, 2022)
DIGITAL CONSTITUTIONALISM: BETWEEN DIGITAL REALITY, TECHNOLOGICAL PERSPECTIVE AND MERE CONSTITUTIONAL DYSTOPIA AREA(S): derecho constitucional. RESUMEN: El objeto de este trabajo es reflexionar sobre el constitucionalismo digital. Ello depende de su difícil relación con la sociedad digital actual, donde la realidad digital trasciende el Derecho Constitucional analógico. Pero podríamos estar ante un auténtico proceso de digitalización del Derecho Constitucional, con el que buscar nuevas formas de proyectar jurídicamente la limitación y organización del poder conforme específicos institutos o principios jurídicos y políticos basados en el progreso y la sociedad digital. ABSTRACT: The scope of this work is to reflect on digital constitutionalism. That depends on it’s difficult relationship with the current digital society, where the digital reality transcends the analogical Constitutional Law. But that could be an authentic process of digitalization of the Constitutional Law, in order to search for new ways of legally projecting the limitation and organization of power, according to specific institutes or legal and political principles, based upon progress and digital society. PALABRAS CLAVE: constitucionalismo; sociedad digital; constitución analógica; digilitación constitucional. KEYWORDS: constitutionalism; digital society; analogical constitution; constitutional digitalization. SUMARIO: 1 Introducción: sociedad digital y derecho constitucional; 2 Constitucionalismo digital como reacción a la realidad digital; 3 Constitucionalismo digital y prospectiva tecnológica; 4 Constitucionalismo digital frente distopía constitucional; 5 Consideraciones finales: la digitalización constitucional. SUMMARY: 1 Introduction: digital society and constitutional law; 2 Digital constitutionalism as a reaction to the digital reality; 3 Digital constitutionalism and technological prospective; 4 Digital constitutionalism vs. constitutional dystopia; 5 Final considerations: constitutional digitization.